Multi-Actor Collaboration in the Implementation of Halal Certification Labeling for Micro and Small Enterprises Amidst Literacy and Service Infrastructure Challenges: A Case Study of Bogor Regency - Salsabila Adawiyah Putri Andini; Muhamad Husain Maruapey; Aji Jumiono (Journal of Economics and Social Sciences (JESS), 2026)
Halal certification is a strategic public policy instrument aimed at consumer protection and the fulfillment of the public’s right to halal product assurance, particularly for Micro and Small Enterprises (MSEs). Nevertheless, its implementation continues to face structural and social challenges, including weak multi-actor collaboration, low levels of halal literacy (approximately 28–30%), and unequal access to halal certification service infrastructure. This study examines how multi-actor collaboration shapes the implementation of halal certification labeling for MSEs, with particular attention to the roles of halal literacy and public service infrastructure readiness. Employing a descriptive qualitative approach, data were collected through semi-structured interviews and policy document analysis and analyzed thematically using the collaborative governance framework of Ansell and Gash (2008). The findings indicate that low halal literacy weakens the initial conditions for collaboration, while limited service infrastructure constrains collaborative processes and delays policy outcomes. Theoretically, this study extends collaborative governance theory by demonstrating how social capacity (halal literacy) and infrastructural readiness function as critical determinants of starting conditions and collaborative processes in public service–oriented policies such as halal certification. Practically, the study recommends strengthening collaboration-based halal literacy programs, expanding equitable certification infrastructure, and integrating public service systems to enhance the effectiveness and sustainability of halal certification implementation for MSEs.